Moral Values in the Folklore of Pan Balang Tamak Story (Sociolinguistic Study) - Citrawati, Putu Evi Wahyu; Wahyu, Gede Eka; Aryani, I Gusti Agung Istri (International Research Journal of Management, IT & Social Sciences, 2016)
In Balinese people, there are allots of folklores that scattered in the society which they call Satua Bali. Narrowly, satua Bali is a story that spread out from generation to generation and words of mouth, it is not known who the creator as well. Meanwhile, in the broad sense, satua Bali is derived from the work of authors, whether it is use Balinese language or ancient Javanese language. There are many satua Bali still survive, one of them is satua Pan Balang Tamak. Pan Balang Tamak is the figure who has very clever character and he does not want to be lost by the villager. Because of his cleverness, the villagers and even the king hate him. And, the attempted to deceive him, but all of their efforts were in vain. Many moral values can be learnt from the story of Pan Balang Tamak, that we are as individual as members of the public should not attempt to cheat, or deceive others. And, the brightness brain that we owned should be used to help others. Data was taken from the story which its existence in society, namely satua Pan Balang Tamak. Then, the data is collected by means of written discourse according to topic above. The method suitable for the study which has written language is a method refers to advanced technique such as technical note (Sudaryanto, 1985:26 1986: 33). Then, the result of data analysis technique use distributional method which works within the scope of language itself without linking it with outside matters.